2016
DOI: 10.1159/000450704
|View full text |Cite
|
Sign up to set email alerts
|

Spleen and Liver Stiffness Is Positively Correlated with the Risk of Esophageal Variceal Bleeding

Abstract: Background/Aims: Portal hypertension (PH) is a common complication of chronic liver disease and results in esophageal and gastric variceal bleeding, which is associated with a high mortality rate. Measurement of the hepatic venous pressure gradient (HVPG) is considered the gold standard for diagnosing PH and estimating the risk of varices and bleeding. In contrast, upper gastrointestinal (GI) endoscopy (UGE) can reliably demonstrate the presence of varices and bleeding. Both measures are invasive, and HVPG is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 30 publications
(44 reference statements)
0
31
1
2
Order By: Relevance
“…Furthermore, several studies (e.g., Buechter et al [21]) demonstrated that the spleen stiffness measurement and the liver stiffness measurement are positively correlated with decompensated portal hypertension, but in our study, we could not correlate our results with the portal hypertension because only for some patients, the value of hepatic venous pressure gradient was available.…”
Section: Discussioncontrasting
confidence: 58%
“…Furthermore, several studies (e.g., Buechter et al [21]) demonstrated that the spleen stiffness measurement and the liver stiffness measurement are positively correlated with decompensated portal hypertension, but in our study, we could not correlate our results with the portal hypertension because only for some patients, the value of hepatic venous pressure gradient was available.…”
Section: Discussioncontrasting
confidence: 58%
“…Large EVs, PHG, PHC, a Child-Pugh system grade B or C severity of liver disease, prior history of endoscopic variceal injection sclerotherapy or ligation, and prior history of acute GI bleeding, as well as a high transient elastography score and a high CT score, have also been associated with an increased risk of PHE [14, 21-25]. Buechter et al [30] reported that the relationship between spleen/liver stiffness measured by elastography and intestinal bleeding with PH [30], and the risk factor of PHE is evaluated by various modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Despite improvements in diagnostics and therapy over the last decades, variceal bleeding still is life-threatening with a 6-week mortality of 10-20% [2,12,13]. In this regard, recent studies indicate that transient elastography is a promising non-invasive screening method for detecting decompensated PH, suggesting a direct positive correlation between spleen and liver stiffness and esophageal variceal bleeding [14,15]. PH-induced UGIB can occur as hemorrhage from PHG, esophageal-or gastric varices.…”
Section: Discussionmentioning
confidence: 99%
“…Five patients were male (56%). The mean Child-Pugh Score at the time of spleen embolization was 5.9 ± 1.3 [5][6][7][8] points, the mean MELD-Score 8.9 ± 2.6 [6][7][8][9][10][11][12][13][14]. All patients had splenomegaly with a mean spleen diameter of 16.6 ± 2.8 [13.3-22.3] cm.…”
Section: Patient Characteristicsmentioning
confidence: 99%